Green synthesis of silver nanoparticle composites with cashew gum and curcumin: Development of nano-structured products based on natural polymer for forensic human identification applications - de Moraes Barbosa Côrtes-Bogniotti, Raissa R; de Oliveira Silva Ribeiro, Fábio; Cardoso, Miguel Gomes; Sá, Bruno Silva; Longo, João Paulo Figueiró; da Silva Carvalho, Daniel; de Oliveira-Neto, Daniel Castilho; Lima, Filipe Camargo Dalmatti Alves; Batagin-Neto, Augusto [UNESP]; Arcanjo, Daniel Dias Rufino; Durazzo, Alessandra; Lucarini, Massimo; et al. (Elsevier, 2025)
The combination of cashew gum (GC) and curcumin (Cur) was explored in the production of Ag nanoparticles (AgNps) by green synthesis, for the development of a fingerprint marker. For this, GC (0.5 % w/v) was added to an aqueous solution of AgNO₃, with and without Cur (1/1). The reduction was carried out in a microwave oven at 2450 MHz for 3 min. AgNps were characterized by UV-vis spectrophotometry, zeta potential, DLS, infrared spectroscopy, computer simulations, AFM and cytotoxicity in HaCat cells. Latent fingermarks on white sulfite-type porous paper were developed after immersion and drying. Synthesis of CG-AgNp and CG-Cur-AgNp preserved the main physicochemical characteristics of CG and Cur. In UV-visible spectrum, it presented bands at 420 nm and 480 nm, with a hydrodynamic diameter of 135.2 nm for CG-AgNp and 175.10 nm for CG-Cur-AgNp. By AFM, the AgNps have a spherical shape with homogeneous diameter, ranging from 31.63 nm (CG-AgNp) and 34.81 nm (CG-Cur-AgNp). Not show significant reduction in cell viability in HaCat cells (3.125-0.781 μM of Ag). It was observed that the revelations at 0 h and 24 h after the production of the IDLs, with 12 points marked with nanoparticles.